Pengaruh Computer Self-Efficacy dan Task-Technology Fit Terhadap penerimaan Penggunaan lnternet - Petra Surya Mega Wijaya (Jurnal Riset Akuntansi dan Keuangan, 2006)
This study examines the correlation between'perceived ease-of-use uari-. able and perceived usefulness variable, beliefs (perceived ease:of-use and perciived usefulness) against behavior intention to !t:e, behavior inteition to use against behavior to use, cornputer self efricaW against perceived e^"ro|-ur", task-teclmolog fit against beliefs, and task+ech' 'nologt fit against behavior intention to use. The model used to answer the iisiarch questions ef tfu study is the Technologt Acceptance Model (fAM). One hundred sixty tltree respondents used base on the question- Lo ipooa among clerk govemment in Daerah Istimewa Yogtakarta in order to test their behaior on the usage of internet' Structural Equation Modet (SEM analysis.results show that the model f"tfiAt goodness of fit criteria. There are-significant.correlations among -task-tu;hnology fit against beliefs and behavior intqntion to use- Surprhingly, theie are no signiJicant correlations between perceived ease- 'of-usi and perceived usefulness variable, beliefs and behavior intention to use, behavior intention to use and behavior to use, and comiriir, t"ilmracy and perceived ease-of-use' Keywords: Computer self-efficacy, task-technology fit, IAM, SEM, interneL clerk government